ANALYSIS OF THE APPLICATION OF SAK ETAP ON THE QUALITY OF FINANCIAL STATEMENTS CASE STUDY AT KPN SETYA GRAHA DESA PENYARINGAN, MENDOYO DISTRICT, JEMBRANA REGENCY - Perdana, I Komang Gandy; Musmini, Lucy Sri; Devi, Sunitha (Proceeding of TEAMS: The International Conference on Tourism, Economic, Accounting, Management and Social Science, 2025)
This study aims to analyze the implementation of SAK ETAP and its impact on the quality of financial statements at KPN Setya Graha. This study uses a descriptive qualitative approach. The data sources for this study are primary data obtained from interviews with KPN Setya Graha employees and secondary data in the form of KPN Setya Graha's Annual Financial Reports from 2022 to 2024. The object of this study is a case study at KPN Setya Graha, located in Penyaringan Village, Mendoyo District, Jembrana Regency. The novelty of this study compared to previous studies lies in its focus on the impact of the implementation of SAK ETAP on the quality of financial statements. The data analysis technique used in this study is data reduction, which involves focusing on the issues at hand, reviewing the notes obtained at the research site, then collecting detailed data to be compiled into a report. The data presentation involves analyzing the obtained data and presenting it in the study. The final data analysis technique is drawing conclusions, where after presenting the data, the researcher draws conclusions related to the results of this study. The results of this study indicate that KPN Setya Graha has implemented SAK ETAP in its financial reporting, which also affects the quality of KPN Setya Graha's financial reports. KPN Setya Graha's financial reports after the implementation of SAK ETAP have become more transparent and easier to understand. In 2022, KPN Setya Graha's annual financial reports were used as examples for KPNs in Jembrana Regency.